1980
DOI: 10.3109/00207458009160484
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Characteristics of Hedgehog Polysensory Cortical Zone

Abstract: The study of the neuronal organization of the hedgehog associative cortical zone revealed that besides primitive characteristics this area possesses a number of progressive features. An electrophysiological approach revealed a great number of polysensory neurons. The method, based on the HRP retrograde axonal transport, enabled us to discover the connections between primitive associative LP and MD thalamic nuclei and the associative cortex. Motor conditioned reflexes connected with visual discrimination as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1983
1983
1994
1994

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…It is suggested that the presence of these neurons reflects the retention of a primitive character in neocortical evolution." Tolchenova and Demyanenko (1975), Demyanenko (1976) and Batuev et al (1980) investigated the so-called polysensory "assoziation" area described by the Russian authors based on Golgi and electron microscopic methods.…”
Section: Histology Histochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…It is suggested that the presence of these neurons reflects the retention of a primitive character in neocortical evolution." Tolchenova and Demyanenko (1975), Demyanenko (1976) and Batuev et al (1980) investigated the so-called polysensory "assoziation" area described by the Russian authors based on Golgi and electron microscopic methods.…”
Section: Histology Histochemistrymentioning
confidence: 99%
“…99). Russian authors (Batuev and Kararnyan 1973;Pirogov 1977;Batuev et al 1980) were especially interested in localizing zones of intersensory integration. They described an association area in the middle of the lateral NEO.…”
Section: Histology Histochemistrymentioning
confidence: 99%